First hepatitis E outbreak in Southeastern Senegal - Bacary Djilocalisse Sadio; Martin Faye; Marco Kaiser; Maryam Diarra; Fanny Balique; Cheikh Tidiane Diagne; Oumar Faye; Moussa Moïse Diagne; Gamou Fall; Oumar Ndiaye; Cheikh Loucoubar; Abdourahmane Sow; et al. (Scientific Reports, 2022)
Abstract The Rapid proliferation of traditional gold mining sites in the Kedougou region has led to massive migration of people from neighbouring West African countries and the establishment of several small villages where poor hygiene and sanitation conditions exist. In this context, a Hepatitis E virus outbreak was reported in Kedougou in 2014 with several cases among the traditional mining workers. Herein, we described epidemiological and laboratory data collected during the outbreak’s investigation from February 2012 to November 2014. Any suspected, contact or probable case was investigated, clinical and epidemiological data were collected. In our study, sera were collected and tested for viral RNA and anti-Hepatitis E virus (HEV) IgM. Archived serum samples from Kedougou were retrospectively screened by real-time polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA). A total of 65 water samples collected from ponds and wells surrounding gold panners' sites and habitats and 75 tissues samples from rats captured in the environment of traditional gold mining sites were also tested. A total of 1617 sera were collected from 698 suspected cases, 862 contacts and 57 persons with missing information. The median age was 20 (1–88 years-old) and the sex ratio was 1.72. An overall rate of 64.62% (1045/1617) of these patients tested positive for HEV with a high case fatality rate in pregnant women. All water samples and animal tissues tested negative for HEV. Our data help not only determining of the beginning of the HEV outbreak to March 2012, but also identifying risk factors associated to its emergence. However, there is a need to implement routine diagnosis, surveillance and training of health personnel in order to reduce mortality especially among pregnant women. In addition, further studies are needed to identify the virus reservoir and environmental risk factors for HEV in the Kedougou region.